PERUVIAN ECONOMIC GROWTH AND CORPORATE SOCIAL RESPONSIBILITY - Palomino Silva, Julio Alberto (2011)
The Private Sector Role in society is changing before the new configuration of global and local economy, so the renewed attitude and meet the needs and challenges. The market is increasingly demanding in terms of protecting the social and environmental context, requires that the companies incorporated within their social responsibility in their institutional policies. This new approach to corporate governance, on the one hand generates a stream of responsible consumption and the other, encourages and supports ethical investment responsibility for their environment. Most countries have achieved a high rate of domestic investment and attract international investment just using this approach, which achieves the stage for investment. In our country, however, this new social role of companies is being implemented at a very basic level, because social responsibility is seen as an unnecessary expense and not as an investment, deteriorate the fact that the social aspect is determining the existence and continuity of the Company, both coexisting in close relationship, where the transformations that occur in one affect the other. Getting a glimpse of this relationship conditional Company - social responsibility, to determine how corporate responsibility is seen in the context of national economic growth, as set forth this new approach and help the company considers its social responsibility as an investment, the objective of this item that fits perfectly with the Millennium Declaration, United Nations, with the Doha Agenda for Development and the Johannesburg Declaration whose purpose is to promote a better distribution of state functions, Enterprise and Civil Society actors achieving development and poverty reduction.